“Crime” in Context: Racialized Physical Space Shifts Person-Perception - James, Drexler (Race and social problems, 2023)
People often assume areas where black people live are dangerous, impoverished, and rundown, whereas they assume White areas to be safe, wealthy, and well-maintained (Bonam et al. in J Exp Psychol Gen 145(11):1561–1582, 2016). These space-focused racial stereotypes shape how people perceive, evaluate, and treat physical space, such as houses and neighborhoods. Further, people often associate specific types of spaces with certain races (e.g., inner-city is Black; suburb is White), making them racial exemplar spaces (Bonam, in Devaluing Black space: Black locations as targets of housing and environmental discrimination, Unpublished doctoral dissertation. Stanford University, Stanford, 2010). The present work expands insight into racialized physical space by showing how Black and White exemplar spaces and White space-focused racial stereotypes shape person-perception. Specifically, we report findings from a vignette study examining how “black” and “criminal” people perceived a target person. This target was black or white and was in a suburban or inner-city neighborhood. We also measured people’s generalized stereotypes about white areas. People thought of the Black versus White person as being more black, which in turn made the target seem more criminal. This relationship was stronger in a suburban versus inner-city neighborhood—likely because being in an inner-city area made the White target seem more black, whereas the black target seemed black no matter where he was. Additionally, the more people thought of white areas as generally safe, wealthy, and well-maintained, the more they criminalized the black—but not white—target in a suburban neighborhood. This study highlights the need to further explore how racialized physical space shapes social perception, and it provides insight into the criminalization and policing of black bodies in white spaces.